Om Tørlægning og Kultivering af Havbugter og Søer. Foredrag, d. 9de Dec. 1868. - Grove, Kammerraad (Tidsskrift for Landøkonomi, 2018)
Om Tørlægning og Kultivering af Havbugter og Søer. Foredrag, d. 9de Dec. 1868.